Polyimide film with low CTE and high glass transition temperature and preparation method thereof

By introducing trifluoromethyl groups and bisamide bonds into the polyimide film, the problem that it is difficult for the polyimide film to achieve high optical transparency and high temperature resistance at the same time is solved, and high glass transition temperature and low Polyimide films with thermal expansion coefficient, suitable for display and semiconductor fields.

CN119119527APending Publication Date: 2024-12-13EAST CHINA ENGINEERING SCIENCE AND TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411262107.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-07-12
Filing Date
2024-09-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

It is difficult for existing polyimide films to achieve high optical transparency and high temperature resistance at the same time, especially in the design of high transparency and high temperature resistance molecular structures, and it is difficult to take into account the high optical transparency and high temperature resistance of the polyimide film.

Method used

By preparing a polyamic acid solution, adding a catalyst and a dehydrating agent, coating it on the substrate, drying and imidizing, reacting with tetracarboxylic dianhydride and diamine in an organic solvent, introducing trifluoromethyl groups and bis Amide bonds improve the thermal dimensional stability and optical properties of polyimides.

Benefits of technology

The high glass transition temperature (Tg) of the polyimide film reaches above 330℃, the thermal expansion coefficient (CTE) is not greater than 40ppm/℃ in the range of 50 to 250℃, the transmittance is not less than 88%, and the yellowness index is Not greater than 3, suitable for display or semiconductor fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005036020170000021
    Figure BDA0005036020170000021
  • Figure BDA0005036020170000022
    Figure BDA0005036020170000022
  • Figure BDA0005036020170000023
    Figure BDA0005036020170000023
Patent Text Reader

Abstract

The invention discloses a polyimide film with low CTE and high glass transition temperature and a preparation method thereof. The preparation method of the polyimide film comprises the following steps: S1, preparing a polyamide acid solution; s2, adding a catalyst and a dehydrating agent into the polyamide acid solution in the step S1, uniformly mixing, coating on a substrate, and drying and imidizing to obtain a polyimide film with low CTE and high glass transition temperature; the polyamide acid solution is prepared by reacting tetracarboxylic dianhydride and diamine in an organic solvent. The glass transition temperature (Tg) can reach 330 DEG C or above, the coefficient of thermal expansion (CTE) is 40 ppm / DEG C or below, the yellowness index is not larger than 3, the transmittance at 550 nm is not smaller than 88%, the haze is not larger than 1.0%, and the optical film can serve as an optical film in the fields of display substrates, liquid crystal displays (LCDs), organic light-emitting diodes (OLEDs) and the like and has high application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a polyimide film with low CTE and high glass transition temperature and a preparation method thereof. Background Art

[0002] In recent years, flexible organic light-emitting diode (OLED) displays have been widely used due to their many advantages such as full solid state, active luminescence, high brightness, high contrast, high response and no viewing angle limitation. Traditional OLED devices use hard glass as their cover plate, resulting in very poor flexibility of the device. At present, the use of polymer film materials instead of glass to prepare bendable and foldable OLEDs is one of the most effective methods. At present, polyimide has attracted much attention due to its superior heat resistance, but the optical transparency of high-temperature resistant polyimide films is often poor, and the high-temperature resistance of transparent modified polyimide is often poor. It is often difficult to achieve high optical transmittance and high-temperature resistance of polyimide films at the same time. In the molecular structure design of highly transparent and high-temperature resistant polyimide, one of the most difficult problems to overcome is how to simultaneously achieve high optical transparency and high-temperature resistance (high Tg, low CTE) of polyimide films. Summary of the invention

[0003] Based on the technical problems existing in the background technology, the present invention proposes a polyimide film with low CTE and high glass transition temperature and a preparation method. The polyimide film has high heat resistance, low linear expansion coefficient and high optical transparency, and can be used as an optical film in the fields of display substrates, liquid crystal displays (LCDs) and organic light emitting diodes (OLEDs), and has high application value.

[0004] The present invention provides a method for preparing a polyimide film with low CTE and high glass transition temperature, and the method steps are as follows:

[0005] S1: preparation of polyamic acid solution;

[0006] S2: adding a catalyst and a dehydrating agent to the polyamic acid solution of S1, mixing well, and coating the mixture on a substrate, and obtaining a polyimide film with low CTE and high glass transition temperature after drying and imidization;

[0007] The polyamic acid solution is prepared by reacting tetracarboxylic dianhydride and diamine in an organic solvent;

[0008] The diamine is composed of chemical formula 1 and chemical formula 2, and the molar percentage of chemical formula 1 is not less than 50%;

[0009] [Chemical formula 1]

[0010]

[0011] [Chemical formula 2]

[0012]

[0013] In the above chemical formula 2, R1 is selected from one of hydrogen, fluorine atom, methyl substituent and trifluoromethyl substituent; R2 is selected from -O- or -NH-; R3 is selected from one of hydrogen, halogen atom, hydroxyl, thiol, nitro, C1-10 alkyl, C1-4 haloalkoxy, C1-10 haloalkyl, cyano and C6-20 aryl; R4 is any one of the following substituents:

[0014]

[0015] Preferably, the tetracarboxylic dianhydride is composed of Chemical Formula 3 and Chemical Formula 4, and the molar percentage of Chemical Formula 3 is not less than 20%;

[0016] [Chemical formula 3]

[0017]

[0018] [Chemical formula 4]

[0019]

[0020] In the above chemical formula 4, Ar is selected from any one of the following groups:

[0021]

[0022] Preferably, the molar ratio of diamine to tetracarboxylic dianhydride is 1:0.9-1.2; and the reaction time of tetracarboxylic dianhydride and diamine is 24-48 hours.

[0023] Preferably, the organic solvent is one or more of acetone, N-methyl-2-pyrrolidone, phenol, dimethylacetamide, dimethylformimine and dimethyl sulfoxide.

[0024] Preferably, the catalyst is one or more of imidazole compounds, benzimidazole compounds, quinolone compounds, pyridine and isoquinoline compounds.

[0025] Preferably, the dehydrating agent is one or more of aliphatic anhydride, aromatic anhydride, N,N'-dialkylcarbodiimide, lower aliphatic halide, halogenated lower aliphatic anhydride, and aromatic sulfonic acid dihalide.

[0026] Preferably, the imidization temperature is 25-350° C., and the time is 1-5 h.

[0027] Preferably, the amount of the catalyst added is 0.1-10 wt % of the total mass of the polymer in the polyamic acid solution; and the amount of the dehydrating agent added is 0.1-10 wt % of the total mass of the polymer in the polyamic acid solution.

[0028] The invention provides a polyimide film with low CTE and high glass transition temperature prepared by the method.

[0029] The polyimide film with low CTE and high glass transition temperature proposed by the present invention is used as a substrate in the display or semiconductor fields.

[0030] Beneficial technical effects of the present invention:

[0031] (1) The triphenylmethane of the present invention introduces a trifluoromethyl group, which has a greater spatial volume and greater molecular polarity and is more advantageous than the fluorine group in improving the optical properties of polyimide. In addition, the present invention introduces a diamide bond into the triphenylmethane structure, and improves the thermal dimensional stability of the polyimide through the hydrogen bonding effect of the amide bond, thereby achieving a molecule that takes into account both transparency and heat resistance.

[0032] (2) The glass transition temperature (Tg) of the polyimide film of the present invention can reach above 330°C, the coefficient of thermal expansion (CTE) is not greater than 40ppm / °C when measured for the second time in the range of 50-250°C, the yellowness index is not greater than 3, the transmittance of the polyimide film at 550nm is not less than 88%, and the haze is not greater than 0.5%. The transparent polyimide film has excellent heat resistance and good optical properties, and can be used as a substrate in the display or semiconductor fields. DETAILED DESCRIPTION

[0033] The present invention will be further explained below in conjunction with specific embodiments.

[0034] The abbreviations of the raw materials used in the examples of the present invention are as follows.

[0035] [Diamine component]

[0036] AB-3FDAM:

[0037]

[0038] EB-3FDAM:

[0039]

[0040] AMB-3FDAM:

[0041]

[0042] DB-3FDAM:

[0043]

[0044] DO-3FDAM:

[0045]

[0046] [Tetracarboxylic dianhydride component]

[0047] CBDA: Cyclobutanetetracarboxylic dianhydride

[0048] 6FDA: Hexafluorodianhydride

[0049] s-BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride

[0050] [Solvent]

[0051] DMAc: N,N-dimethylacetamide

[0052] The film performance test method is as follows:

[0053] (1) Determination of dynamic viscosity: The test was conducted using the ASTM D7042 test method.

[0054] (2) Determination of light transmittance and haze: Tested using the GB / T 2410-2008 test method;

[0055] (3) Determination of b* and yellowness index: The yellowness index (YI, ASTM E 313) of the PI film was measured using a colorimeter (PS2050) from Tri-Nex Co., Ltd. to test and evaluate the color of the polyimide film. According to the D65 standard light source and the 2° standard observation angle, the CIE (L*, a*, b*) colorimetric evaluation system was used, which includes three characteristic parameters: L* (0-100, dark and bright), a* (negative, positive, green-red) and b* (negative, positive, blue-yellow). At the same time, the yellowing index (YI) of the sample was provided. The film thickness was about 30 μm (±3 μm).

[0056] (4) Determination of glass transition temperature (Tg): Tested using the GB / T 40396-2021 test method.

[0057] (5) Determination of coefficient of thermal expansion (CTE): Tested using the ISO 11359-2:2021 test method.

[0058] Example 1

[0059] In a 500 mL reactor equipped with a stirrer, nitrogen protection and a temperature controller, dimethylacetamide (DMAc) was added as a solvent. Subsequently, TFMB (0.08 mol) and AB-3FDAM (0.02 mol) were added and stirred at a constant speed to obtain a clear diamine solution. Then, (1.0 mol) of 6FDA was added to the above diamine solution. The resulting mixture was reacted at room temperature for 24 hours to obtain a polyamic acid solution 1 with a solid content of 20 wt% and a rotational viscosity of 50000 mPa·s at 25°C.

[0060] Add dehydrating agent acetic anhydride, catalyst isoquinoline and organic solvent DMAc (accounting for 50wt% of polyamic acid) in a mass ratio of 4:1:5 to the polyamic acid solution, and stir for 30 minutes; apply the obtained mixed solution to a glass substrate, heat directly on the glass substrate from room temperature to 330°C, remove the solvent and complete imidization to obtain a colorless and transparent polyimide film / glass laminate. Then, immerse the obtained polyimide film / glass laminate in water, then peel off and dry to obtain a polyimide film with a film thickness of 35μm.

[0061] Example 2

[0062] In a 500 mL reactor equipped with a stirrer, nitrogen protection and a temperature controller, dimethylacetamide (DMAc) was added as a solvent. Subsequently, TFMB (0.08 mol) and EB-3FDAM (0.02 mol) were added and stirred at a constant speed to obtain a clear diamine solution. Then, (1.0 mol) of 6FDA was added to the above diamine solution. The resulting mixture was reacted at room temperature for 24 hours to obtain a polyamic acid solution 2 with a solid content of 20 wt% and a rotational viscosity of 50000 mPa·s at 25°C.

[0063] Add dehydrating agent acetic anhydride, catalyst isoquinoline and organic solvent DMAc (accounting for 50wt% of polyamic acid) in a mass ratio of 4:1:5 to the polyamic acid solution, and stir for 30 minutes; apply the obtained mixed solution to a glass substrate, heat directly on the glass substrate from room temperature to 330°C, remove the solvent and complete imidization to obtain a colorless and transparent polyimide film / glass laminate. Then, immerse the obtained polyimide film / glass laminate in water, then peel off and dry to obtain a polyimide film with a film thickness of 35μm.

[0064] Example 3

[0065] In a 500 mL reactor equipped with a stirrer, nitrogen protection and a temperature controller, dimethylacetamide (DMAc) was added as a solvent. Subsequently, TFMB (0.08 mol) and AMB-3FDAM (0.02 mol) were added and stirred at a constant speed to obtain a clear diamine solution. Then, 6FDA (0.10 mol) was added to the above diamine solution. The resulting mixed solution was reacted at room temperature for 24 hours to obtain a polyamic acid solution 3 with a solid content of 20 wt% and a rotational viscosity of 50000 mPa·s at 25°C.

[0066] Add dehydrating agent acetic anhydride, catalyst isoquinoline and organic solvent DMAc (accounting for 50wt% of polyamic acid) in a mass ratio of 4:1:5 to the polyamic acid solution, and stir for 30 minutes; apply the obtained mixed solution to a glass substrate, heat directly on the glass substrate from room temperature to 330°C, remove the solvent and complete imidization to obtain a colorless and transparent polyimide film / glass laminate. Then, immerse the obtained polyimide film / glass laminate in water, then peel off and dry to obtain a polyimide film with a film thickness of 35μm.

[0067] Example 4

[0068] In a 500 mL reactor equipped with a stirrer, nitrogen protection and a temperature controller, dimethylacetamide (DMAc) was added as a solvent. Subsequently, TFMB (0.08 mol) and DB-3FDAM (0.02 mol) were added and stirred at a constant speed to obtain a clear diamine solution. Then, 6FDA (0.10 mol) was added to the above diamine solution. The resulting mixed solution was reacted at room temperature for 24 hours to obtain a polyamic acid solution 4 with a solid content of 20 wt% and a rotational viscosity of 50000 mPa·s at 25°C.

[0069] Add dehydrating agent acetic anhydride, catalyst isoquinoline and organic solvent DMAc (accounting for 50wt% of polyamic acid) in a mass ratio of 4:1:5 to the polyamic acid solution, and stir for 30 minutes; apply the obtained mixed solution to a glass substrate, heat directly on the glass substrate from room temperature to 330°C, remove the solvent and complete imidization to obtain a colorless and transparent polyimide film / glass laminate. Then, immerse the obtained polyimide film / glass laminate in water, then peel off and dry to obtain a polyimide film with a film thickness of 35μm.

[0070] Example 5

[0071] In a 500 mL reactor equipped with a stirrer, nitrogen protection and a temperature controller, dimethylacetamide (DMAc) was added as a solvent. Subsequently, TFMB (0.08 mol) and DO-3FDAM (0.02 mol) were added and stirred at a constant speed to obtain a clear diamine solution. Then, 6FDA (0.10 mol) was added to the above diamine solution. The resulting mixed solution was reacted at room temperature for 24 hours to obtain a polyamic acid solution 5 with a solid content of 20 wt% and a rotational viscosity of 50000 mPa·s at 25°C.

[0072] Add dehydrating agent acetic anhydride, catalyst isoquinoline and organic solvent DMAc (accounting for 50wt% of polyamic acid) in a mass ratio of 4:1:5 to the polyamic acid solution, and stir for 30 minutes; apply the obtained mixed solution to a glass substrate, heat directly on the glass substrate from room temperature to 330°C, remove the solvent and complete imidization to obtain a colorless and transparent polyimide film / glass laminate. Then, immerse the obtained polyimide film / glass laminate in water, then peel off and dry to obtain a polyimide film with a film thickness of 35μm.

[0073] Example 6

[0074] In a 500 mL reactor equipped with a stirrer, nitrogen protection and a temperature controller, dimethylacetamide (DMAc) was added as a solvent. Subsequently, TFMB (0.07 mol) and DO-3FDAM (0.03 mol) were added and stirred at a constant speed to obtain a clear diamine solution. Then, (1.0 mol) of CBDA was added to the above diamine solution. The resulting mixture was reacted at room temperature for 24 hours to obtain a polyamic acid solution 6 with a solid content of 20 wt% and a rotational viscosity of 50000 mPa·s at 25°C.

[0075] Add dehydrating agent acetic anhydride, catalyst isoquinoline and organic solvent DMAc (accounting for 50wt% of polyamic acid) in a mass ratio of 4:1:5 to the polyamic acid solution, and stir for 30 minutes; apply the obtained mixed solution to a glass substrate, heat directly on the glass substrate from room temperature to 330°C, remove the solvent and complete imidization to obtain a colorless and transparent polyimide film / glass laminate. Then, immerse the obtained polyimide film / glass laminate in water, then peel off and dry to obtain a polyimide film with a film thickness of 35μm.

[0076] Example 7

[0077] In a 500 mL reactor equipped with a stirrer, nitrogen protection and a temperature controller, dimethylacetamide (DMAc) was added as a solvent. Subsequently, TFMB (0.05 mol) and DO-3FDAM (0.05 mol) were added and stirred at a constant speed to obtain a clear diamine solution. Then, s-BPDA (1.0 mol) was added to the above diamine solution. The resulting mixture was reacted at room temperature for 24 hours to obtain a polyamic acid solution 7 with a solid content of 20 wt% and a rotational viscosity of 50000 mPa·s at 25°C.

[0078] Add dehydrating agent acetic anhydride, catalyst isoquinoline and organic solvent DMAc (accounting for 50wt% of polyamic acid) in a mass ratio of 4:1:5 to the polyamic acid solution, and stir for 30 minutes; apply the obtained mixed solution to a glass substrate, heat directly on the glass substrate from room temperature to 330°C, remove the solvent and complete imidization to obtain a colorless and transparent polyimide film / glass laminate. Then, immerse the obtained polyimide film / glass laminate in water, then peel off and dry to obtain a polyimide film with a film thickness of 35μm.

[0079] Example 8

[0080] In a 500 mL reactor equipped with a stirrer, nitrogen protection and a temperature controller, dimethylacetamide (DMAc) was added as a solvent. Subsequently, TFMB (0.08 mol) and DO-3FDAM (0.02 mol) were added and stirred at a constant speed to obtain a clear diamine solution. Then, 6FDA (0.08 mol) and CBDA (0.02 mol) were added to the above diamine solution in sequence. The resulting mixed solution was reacted at room temperature for 24 hours to obtain a polyamic acid solution 8 with a solid content of 20 wt% and a rotational viscosity of 50,000 mPa·s at 25°C.

[0081] Add dehydrating agent acetic anhydride, catalyst isoquinoline and organic solvent DMAc (accounting for 50wt% of polyamic acid) in a mass ratio of 4:1:5 to the polyamic acid solution, and stir for 30 minutes; apply the obtained mixed solution to a glass substrate, heat directly on the glass substrate from room temperature to 330°C, remove the solvent and complete imidization to obtain a colorless and transparent polyimide film / glass laminate. Then, immerse the obtained polyimide film / glass laminate in water, then peel off and dry to obtain a polyimide film with a film thickness of 35μm.

[0082] Example 9

[0083] In a 500 mL reactor equipped with a stirrer, nitrogen protection and a temperature controller, dimethylacetamide (DMAc) was added as a solvent. Subsequently, TFMB (0.08 mol) and DO-3FDAM (0.02 mol) were added and stirred at a constant speed to obtain a clear diamine solution. Then, 6FDA (0.08 mol) and s-BPDA (0.02 mol) were added to the above diamine solution in sequence. The resulting mixed solution was reacted at room temperature for 24 hours to obtain a polyamic acid solution 9 with a solid content of 20 wt% and a rotational viscosity of 50000 mPa·s at 25°C.

[0084] Add dehydrating agent acetic anhydride, catalyst isoquinoline and organic solvent DMAc (accounting for 50wt% of polyamic acid) in a mass ratio of 4:1:5 to the polyamic acid solution, and stir for 30 minutes; apply the obtained mixed solution to a glass substrate, heat directly on the glass substrate from room temperature to 330°C, remove the solvent and complete imidization to obtain a colorless and transparent polyimide film / glass laminate. Then, immerse the obtained polyimide film / glass laminate in water, then peel off and dry to obtain a polyimide film with a film thickness of 35μm.

[0085] Example 10

[0086] In a 500 mL reactor equipped with a stirrer, nitrogen protection and a temperature controller, dimethylacetamide (DMAc) was added as a solvent. Subsequently, TFMB (0.08 mol) and DO-3FDAM (0.02 mol) were added and stirred at a constant speed to obtain a clear diamine solution. Then, CBDA (0.08 mol) and s-BPDA (0.02 mol) were added to the above diamine solution in sequence. The resulting mixed solution was reacted at room temperature for 24 hours to obtain a polyamic acid solution 10 with a solid content of 20 wt% and a rotational viscosity of 50000 mPa·s at 25°C.

[0087] Add dehydrating agent acetic anhydride, catalyst isoquinoline and organic solvent DMAc (accounting for 50wt% of polyamic acid) in a mass ratio of 4:1:5 to the polyamic acid solution, and stir for 30 minutes; apply the obtained mixed solution to a glass substrate, heat directly on the glass substrate from room temperature to 330°C, remove the solvent and complete imidization to obtain a colorless and transparent polyimide film / glass laminate. Then, immerse the obtained polyimide film / glass laminate in water, then peel off and dry to obtain a polyimide film with a film thickness of 35μm.

[0088] Comparative Example 1

[0089] In a 500 mL reactor equipped with a stirrer, nitrogen protection and a temperature controller, dimethylacetamide (DMAc) was added as a solvent. Subsequently, TFMB (1.0 mol) was added and stirred at a constant speed to obtain a clear diamine solution. Then, (1.0 mol) of 6FDA was added to the above diamine solution. The resulting mixed solution was reacted at room temperature for 24 hours to obtain a polyamic acid solution 11 with a solid content of 20 wt% and a rotational viscosity of 50000 mPa·s at 25°C.

[0090] Add dehydrating agent acetic anhydride, catalyst isoquinoline and organic solvent DMAc (accounting for 50wt% of polyamic acid) in a mass ratio of 4:1:5 to the polyamic acid solution, and stir for 30 minutes; apply the obtained mixed solution to a glass substrate, heat directly on the glass substrate from room temperature to 330°C, remove the solvent and complete imidization to obtain a colorless and transparent polyimide film / glass laminate. Then, immerse the obtained polyimide film / glass laminate in water, then peel off and dry to obtain a polyimide film with a film thickness of 35μm.

[0091] Comparative Example 2

[0092] In a 500 mL reactor equipped with a stirrer, nitrogen protection and a temperature controller, dimethylacetamide (DMAc) was added as a solvent. Subsequently, TFMB (0.08 mol) and DO-3FDAM (0.02 mol) were added and stirred at a constant speed to obtain a clear diamine solution. Then, CBDA (1.0 mol) was added to the above diamine solution. The resulting mixture was reacted at room temperature for 24 hours to obtain a polyamic acid solution 12 with a solid content of 20 wt% and a rotational viscosity of 50,000 mPa·s at 25°C.

[0093] Add dehydrating agent acetic anhydride, catalyst isoquinoline and organic solvent DMAc (accounting for 50wt% of polyamic acid) in a mass ratio of 4:1:5 to the polyamic acid solution, and stir for 30 minutes; apply the obtained mixed solution to a glass substrate, heat directly on the glass substrate from room temperature to 330°C, remove the solvent and complete imidization to obtain a colorless and transparent polyimide film / glass laminate. Then, immerse the obtained polyimide film / glass laminate in water, then peel off and dry to obtain a polyimide film with a film thickness of 35μm.

[0094] Comparative Example 3

[0095] In a 500 mL reactor equipped with a stirrer, nitrogen protection and a temperature controller, dimethylacetamide (DMAc) was added as a solvent. Subsequently, TFMB (0.08 mol) and DO-3FDAM (0.02 mol) were added and stirred at a constant speed to obtain a clear diamine solution. Then, s-BPDA (1.0 mol) was added to the above diamine solution. The resulting mixed solution was reacted at room temperature for 24 hours to obtain a polyamic acid solution 13 with a solid content of 20 wt% and a rotational viscosity of 50,000 mPa·s at 25°C.

[0096] Add dehydrating agent acetic anhydride, catalyst isoquinoline and organic solvent DMAc (accounting for 50wt% of polyamic acid) in a mass ratio of 4:1:5 to the polyamic acid solution, and stir for 30 minutes; apply the obtained mixed solution to a glass substrate, heat directly on the glass substrate from room temperature to 330°C, remove the solvent and complete imidization to obtain a colorless and transparent polyimide film / glass laminate. Then, immerse the obtained polyimide film / glass laminate in water, then peel off and dry to obtain a polyimide film with a film thickness of 35μm.

[0097] Table 1 Proportions of diamine and tetracarboxylic dianhydride in various examples and comparative examples

[0098]

[0099]

[0100] Table 2 Performance test results of polyimide films of various embodiments and comparative examples

[0101] Test items 550nm transmittance / % Haze / % Yellowness Index CTE / ppm / K Tg / ℃ Example 1 90 0.84 1.4 32 339 Example 2 88 0.82 1.5 37 333 Example 3 89 0.86 1.6 36 335 Example 4 89 0.88 2.4 21 365 Example 5 88 0.78 2.8 22 362 Example 6 91 0.80 2.6 17 363 Example 7 87 0.81 2.9 15 366 Example 8 89 0.82 1.9 18 365 Example 9 88 0.85 2.8 12 359 Example 10 88 0.87 2.2 26 340 Comparative Example 1 92 0.88 0.8 55 327 Comparative Example 2 87 0.95 4.5 15 335 Comparative Example 3 85 0.89 5.9 18 345

[0102] It can be seen from the test results in Table 2 that the polyimide films of Examples 1 to 10 of the present invention all have high transparency, yellowness index not greater than 3, transmittance at 550nm not less than 88%, haze not greater than 1.0%, and glass transition temperature above 330°C, while the coefficient of thermal expansion (CTE) of the polyimide film of the present invention is below 40ppm / °C. By comparing Examples 1, 2, 3, 4 and 5 with Comparative Example 1, it can be seen that when a triphenylmethane structure containing a bisamide bond or a bisester bond is introduced on the basis of Comparative Example 1, the glass transition temperature and thermal dimensional stability can be significantly improved and the optical properties are not significantly reduced. By comparing Comparative Examples 2 and 3 of Examples 3, 8, 9 and 10, it can be seen that when aliphatic dianhydride CBDA is appropriately added to the dianhydride, it is beneficial to increase the thermal dimensional stability of the film without reducing the optical properties of the film. Therefore, the polyimide film described in the present invention can optimize the film performance by adjusting the content of triphenylmethanes and the ratio of different dianhydrides, so that the film has the characteristics of high heat resistance, transparency and high modulus, and can be used as a display substrate or optical film in the fields of liquid crystal displays (LCDs), organic light emitting diodes (OLEDs) and other fields. Base material.

Claims

1. A method for preparing a polyimide film with low CTE and high glass transition temperature, characterized in that: The steps are as follows: S1: preparation of polyamic acid solution; S2: adding a catalyst and a dehydrating agent to the polyamic acid solution of S1, mixing well, and coating the mixture on a substrate, and obtaining a polyimide film with low CTE and high glass transition temperature after drying and imidization; The polyamic acid solution is prepared by reacting tetracarboxylic dianhydride and diamine in an organic solvent; The diamine is composed of chemical formula 1 and chemical formula 2, and the molar percentage of chemical formula 1 is not less than 50%; [Chemical formula 1] [Chemical formula 2] In the above chemical formula 2, R1 is selected from one of hydrogen, fluorine atom, methyl substituent and trifluoromethyl substituent; R2 is selected from -O- or -NH-; R3 is selected from one of hydrogen, halogen atom, hydroxyl, thiol, nitro, C1-10 alkyl, C1-4 haloalkoxy, C1-10 haloalkyl, cyano and C6-20 aryl; R4 is any one of the following substituents:

2. The method for preparing a polyimide film with low CTE and high glass transition temperature according to claim 1, characterized in that: The tetracarboxylic dianhydride is composed of Chemical Formula 3 and Chemical Formula 4, and the molar percentage of Chemical Formula 3 is not less than 20%; [Chemical formula 3] [Chemical formula 4] In the above chemical formula 4, Ar is selected from any one of the following groups:

3. The method for preparing a polyimide film with low CTE and high glass transition temperature according to claim 1, characterized in that: The molar ratio of diamine to tetracarboxylic dianhydride is 1:0.9-1.2; the reaction time of tetracarboxylic dianhydride and diamine is 24-48 hours.

4. The method for preparing a polyimide film with low CTE and high glass transition temperature according to claim 1, characterized in that: The organic solvent is one or more of acetone, N-methyl-2-pyrrolidone, phenol, dimethylacetamide, dimethylformimine and dimethyl sulfoxide.

5. The method for preparing a polyimide film with low CTE and high glass transition temperature according to claim 1, characterized in that: The catalyst is one or more of imidazole compounds, benzimidazole compounds, quinolone compounds, pyridine and isoquinoline compounds.

6. The method for preparing a polyimide film with low CTE and high glass transition temperature according to claim 1, characterized in that: The dehydrating agent is one or more of aliphatic anhydride, aromatic anhydride, N,N'-dialkylcarbodiimide, lower aliphatic halide, halogenated lower aliphatic anhydride, and aromatic sulfonic acid dihalide.

7. The method for preparing a polyimide film with low CTE and high glass transition temperature according to claim 1, characterized in that: The temperature of imidization is 25-350°C, and the time is 1-5h.

8. The method for preparing a polyimide film with low CTE and high glass transition temperature according to claim 1, characterized in that: The added amount of the catalyst is 0.1-10wt% of the total mass of the polymer in the polyamic acid solution; the added amount of the dehydrating agent is 0.1-10wt% of the total mass of the polymer in the polyamic acid solution.

9. A polyimide film with low CTE and high glass transition temperature prepared by the method according to any one of claims 1 to 8.

10. The polyimide film with low CTE and high glass transition temperature as claimed in claim 9 is used as a substrate in the display or semiconductor fields.